PEMANTAUAN DAN EVALUASI KEGIATAN PEMBERDAYAAN DAN PENGEMBANGAN KETANGGUHAN MASYARAKAT DESA TANGGUH BENCANA DI PROVINSI RIAU - Ratih Setyo Rini; Puji Yuniarti; Wiwin Wianti (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
This research is descriptive qualitative with the aim of describing the Empowerment and Development of Community Resilience Activities in Disaster Resilient Villages in Riau Province. To get a complete picture and to be able to provide evaluations on several aspects of the assessment, monitoring of the implementation of activities is carried out through direct interviews with activity actors and reading literature through documents and reports on the implementation of activities. In general, all stages of Activities Empowerment and Development of Community Resilience in Disaster Resilient Villages has been carried out in Riau Province, namely in Siak Regency and Kampar Regency. In Siak Regency, activities were carried out in 3 (three) sub-districts and 3 (three) villages/kelurahan. Meanwhile in Kampar Regency, activities were carried out in 2 (two) sub-districts and 2 (two) villages/kelurahan. Empowerment and Development of Community Resilience in Disaster Resilient Villages in Riau Province. In general, it has achieved its objectives, but during the implementation of the activity stages, it has faced several problems. One suggestion for improving activities is to provide a budget for training (continuity) in forest fire control for government officials, village volunteers and forestry companies as well as communities around the forest.